"The Other Side of Imperialism": The Comic Monologue in Angela Carter's Late Fiction. (21st January 2021) - Harris, Scott
Abstract: This essay takes seriously Angela Carter's playful treatment of race and imperialism across her late fiction. It argues that Carter's representation of popular theatrical culture as a demotic variety of Englishness reveals a paradoxical tension at the heart of her politics: namely, the idea that one can sustain a serious antiracist or anti-imperialist politics while simultaneously taking pleasure in the popular forms that underwrite "Englishness" as a demographic category. In reading the comic monologue as a central feature of Carter's narrative strategy across her last two novels, Nights at the Circus (1984) and Wise Children (1991), and her short story, "Black Venus" (1980), this essay suggests that Carter adopts the critical edge of comic performance to establish a dissenting, oppositional relationship to imperial culture and its legacies .